2020
DOI: 10.1021/acssuschemeng.0c02996
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Biogas Upgrading and Fertilizer Recovery in Anaerobic Digestion from Laminaria Hydrothermal Carbonization Process Water by Fe-Modified Hydrochar

Abstract: Hydrothermal carbonization (HTC) combined with anaerobic digestion (AD) is a cost-effective process to simultaneously treat biomass wastes for hydrochar production, energy recovery, and wastewater treatment. However, low fermentation efficiency and high carbon dioxide content in biogas are tricky problems of this process. This study developed a novel strategy based on Fe-modified hydrochar (Fe-HC) for in situ biogas upgrading and fertilizer recovery by AD of macroalgae Laminaria HTC process water. The daily yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It has been reported that some microorganisms tended to absorb metal onto their cell surface through a number of proton- and metal-active surface functional groups such as amine and carboxyl groups . In addition, negatively charged exopolysaccharide around the surface cells also favored metal binding to form a stable three-dimensional structure …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that some microorganisms tended to absorb metal onto their cell surface through a number of proton- and metal-active surface functional groups such as amine and carboxyl groups . In addition, negatively charged exopolysaccharide around the surface cells also favored metal binding to form a stable three-dimensional structure …”
Section: Results and Discussionmentioning
confidence: 99%
“…24 In addition, negatively charged exopolysaccharide around the surface cells also favored metal binding to form a stable threedimensional structure. 25 The elemental composition of the biofilm was further determined by X-ray photoemission spectroscopy (XPS). As shown in Table S2, an increment of N, O, and S content was detected with both electrodes compared to the raw carbon matrix, new elements of Ni, Fe, and P were present, especially on Bio FeCF.…”
Section: Mechanism Analysis Of Feinvolved Electrons Transfermentioning
confidence: 99%
“…Hence, microbial aggregation contributes to the reinforcement of direct contact with syntrophic microbes, thereby further strengthening the DIET process [37]. Wang et al found that biochar increased the content of EPSs by 40.5% and excess EPSs facilitated the formation of a robust three-dimensional structure to accelerate the aggregation of sludge into granules [109]. The formation of granular sludge created a situation for the potential DIET process to develop.…”
Section: Facilitated Microbial Aggregationmentioning
confidence: 99%